2010
DOI: 10.4314/afrrev.v3i5.51142
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Family Functions and Juvenile Delinquency: A Case of Nakuru Municipality, Kenya

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Kalff et al conclude that parental education has a critical impact on mental health and the behavior of children. This finding is similar to a Kenyan study by Muola, Ndung'u, and Ngesa (2009) who also found an inverse relationship between juvenile delinquency and SES among children (n = 148). Similarly, a Nigerian study by Ekpo and Ajake (2013) also found family SES (i.e., measured in terms of rich families and poor families) to greatly influence children's (n = 600) delinquency, whereby children from low SES were more likely to be involved in delinquent behaviors compared with those of higher SES.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Kalff et al conclude that parental education has a critical impact on mental health and the behavior of children. This finding is similar to a Kenyan study by Muola, Ndung'u, and Ngesa (2009) who also found an inverse relationship between juvenile delinquency and SES among children (n = 148). Similarly, a Nigerian study by Ekpo and Ajake (2013) also found family SES (i.e., measured in terms of rich families and poor families) to greatly influence children's (n = 600) delinquency, whereby children from low SES were more likely to be involved in delinquent behaviors compared with those of higher SES.…”
Section: Introductionsupporting
confidence: 90%
“…Although difficult to interpret, these null findings could suggest that parents with high income were perhaps absent and/or spend less time with their children given their time-consuming and demanding work, consequently unable to provide the necessary guidance and support (Krueger et al, 2009). Likewise, parents with low income are perhaps financial strained, consequently unable to properly care for their children, which could further remove them from being active in the lives of their children (Ekpo & Ajake, 2013;Muola et al, 2009). It is likely that children from low SES groups have a cultural deficiency as they are likely to be deprived of several necessary resources through low income and lack of parental education, which consequently could limit access to and create deficits in much-needed knowledge around how to reduce negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, many studies rely primarily on small, male-only, non-representative samples, or employ no comparison groups, thus raising questions about the generalizability of any observed family size and delinquency relationship. For example, reliance on male-only samples is common (Biles & Challinger, 1981; Farrington, 1987; Farrington et al, 2009; Glueck & Glueck, 1950; Heck & Walsh, 2000; Lees & Newson, 1954; Parrott & Strongman, 1984; Sampson & Laub, 1994; Slawson, 1925; Walsh & Petee, 1987; West & Farrington, 1973), and many studies focus exclusively on known delinquents (Andrew, 1978; Biles & Challinger, 1981; Heck & Walsh, 2000; Lees & Newson, 1954; Muola et al, 2009; Touliatos & Lindholm, 1980). The generalizability of the study findings thus remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Nakuru Municipality by Muola, Ngung'u and Ngesa (2009) established that older siblings serve as "agents of socialisation" who teach younger siblings by example about informal social behaviours such as how to act around friends. Muola et al (2009) noted that younger siblings are also highly susceptible to acquiring older siblings' maladjusted habits including underage drinking and smoking. According to Muola et al (2009), younger siblings with diverse interests or more dominant personalities can affect older siblings similarly and thus parents must be able to distinguish between healthy sibling relationships and damaging abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Muola et al (2009) noted that younger siblings are also highly susceptible to acquiring older siblings' maladjusted habits including underage drinking and smoking. According to Muola et al (2009), younger siblings with diverse interests or more dominant personalities can affect older siblings similarly and thus parents must be able to distinguish between healthy sibling relationships and damaging abuse. Muola et al's findings further assert that sibling rivalry is a normal and mostly harmless part of growing up.…”
Section: Introductionmentioning
confidence: 99%